ХОРАЗМ ВИЛОЯТИ ТУПРОҚ-ИҚЛИМ ШАРОИТИДА CALENDULA OFFICINALIS L.НИНГ ЭКОЛОГИК ОМИЛЛАРИГА МУНОСАБАТИ (Proceedings of International Educators Conference, 2023)
This article discusses the Based on the results obtained, it was proved that Khorezm region has the potential to expand the crop area due to the successful completion of all stages of ontogeny under the conditions of introduction for the medicinal plant calendula (Calendula officinalis L.), seed reproduction, pest control.